Urbanization Primer / Project Assessment, Site Analysis, Design Criteria for Site and Services or Similar Dwelling Environments in Developing Areas, with a Documentary Collection of Photographs on Urbanization - Caminos Horacio; Goethert Reinhard (The MIT Press, 1978)
Acknowledgements, Preface, Introduction, Project Assessment, Guidelines for Identification, Procedures for Evaluation, Site Analysis, Size and Shape, Boundaries, Views, Soil, Climate, Flooding, Land Tenure, Utilities, Refuse Collection, Income Groups, Land Utilization, Land Development, Design Criteria, The Models, The Matrix, Water Supply, Sewage Disposal, Electricity and Street Lighting, Appendix, Utilities: Cost Data, Illustrations, Abbreviations, Units of Measurment, Glossary, Bibliography, Index.